Effectiveness of the Teaching Strategies and Pronunciation in Improving Students’ Reading Comprehension Skills - One Lailla Trisanti; Nyimas Novia Rahmawati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
In this study, the researcher used quantitative approach with quasi-experimental method using 2x3 factorial design. The population in this study was class XI of SMAN 4 Kota Serang which amounted to 565 students with samples selected by random sampling which amounted to 90 students, namely class XI MIA 1 and XI MIA 2. The instruments used were pre-test and post-test with the form of 20 multiple choice questions and 5 essays to assess students’ pronunciation as a comparison (B) in a 2x3 factorial design. For data collection techniques in this study using pre-test and post-test. Meanwhile, for the data analysis used in this research is the normality test, homogeneity test, descriptive statitistics, two-way ANOVA, and tukey test. The results showed a significant difference between the post-test of the experimental group and the control group. The F0 value is 3.397 and Sig. is 0.038 < 0.05. Thus, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. That is, there is an interaction between teaching strategies and pronunciation levels in the skill of improving students’ reading comprehension.